Gambaran Mindfulness Mahasiswa Psikologi UIN Walisongo dalam Menjaga Kesehatan Mental - Amalia Zulfa; Febby Fariska; Abdul Malik Karim Amrullah; Dewi Khurun Aini (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
In a state of mindfulness, a person deliberately focuses completely on one particular thing or activity, without being distracted by attention to other things. This research uses qualitative methods, especially phenomenology with the aim of understanding the picture of mindfulness of Psychology students at UIN Walisongo in maintaining mental health. Data was obtained through interviews, observation and documentation, with a population of all Psychology students at UIN Walisongo and a sample of 5 informants selected using purposive sampling. The research results showed that 4 informants had a good picture of mindfulness because they fulfilled three main aspects, namely acting with awareness, observing, and accepting without judgment. One informant, although he had a good picture of mindfulness in the first two aspects, was still lacking in the aspect of accepting without judgment. These findings provide an overview of the level of mindfulness among Psychology students at UIN Walisongo, with potential implications in the development of mental health strategies or interventions in academic environments. These results provide valuable insight for the development of mental health intervention strategies among Psychology students at UIN Walisongo.